Hormone replacement therapy in brain-dead organ donors: a comprehensive review with an emphasis on traumatic brain injury. Issue 4 (April 2019) - Turco, Lauren M.; Glorsky, Steven L.; Winfield, Robert D.
Abstract : BACKGROUND: Organ shortage is an ongoing problem in the United States. Most donor organs are procured following brain death and a significant portion of brain-dead donors result from devastating brain injury. Without a standard practice for hormone replacement therapy (HRT) in the setting of brain death, a comprehensive review of the literature was deemed necessary. METHODS: A search of published literature was conducted with terms "TBI" or "brain injury" or "head injury" AND "hormone" or "management" AND "organ" AND "donor" or "donation." Abstracts and full texts were screened for relevance and inclusion of information on HRT. Additional studies were selected from references cited within these. Excluded studies were non-English, nonhuman based, or had small sample size, (i.e., case reports or series with fewer than five subjects). RESULTS: Fifteen studies were selected for inclusion and contained Level III or Level IV evidence. Combinations of thyroid hormone, insulin, and corticosteroids were the most commonly cited HRT. Ninety-three percent of studies found a significant increase in organ procurement rate among donors who received HRT. Hormone replacement therapy was administered after brain death declaration in eight studies. Only two studies specifically explored the effects of starting HRT earlier and identified even greater procurement rates. Four studies were specific to traumatic brain injury (TBI); the remaining 11 studies involved TBI in 22% to 89% of the sample. CONCLUSION: Organ shortage remains a growing problem in the United States. Donor management including HRT has been proposed to combat the endocrine derangement associated with brain death and, in particular, TBI. While the existing literature reported compelling outcomes using HRT, there remains a need for further Level I and Level II evidence studies to define optimal practice. LEVEL OF EVIDENCE: Review article, level IV.